2023
DOI: 10.1039/d3na00382e
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanisms of monolayer hexagonal boron nitride (h-BN) on metal surfaces: theoretical perspectives

Abstract: Two-dimensional hexagonal boron nitride (h-BN) has appeared as a promising material in diverse areas of applications, including as an excellent substrate for graphene devices, deep-ultraviolet emitters, and tunneling barriers, thanks...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 348 publications
(674 reference statements)
0
3
0
Order By: Relevance
“…During the initial growth, the clusters of 2D vdW materials adopt the energy-favored sites, whose registry is well preserved upon further growth owing to the strong interaction between the edge atoms and the underlying substrates. 44,45 In addition, edge structures play a critical role in controlling the growth kinetics and morphological evolution in 2D vdW materials. 46–51 There have been several review articles covering the role of geometries, energetics and stabilities of different edges of 2D nuclei and also on the role of different growth parameters ( e.g.…”
Section: Driving Forces For the On-substrate Nucleation And Growth Of...mentioning
confidence: 99%
“…During the initial growth, the clusters of 2D vdW materials adopt the energy-favored sites, whose registry is well preserved upon further growth owing to the strong interaction between the edge atoms and the underlying substrates. 44,45 In addition, edge structures play a critical role in controlling the growth kinetics and morphological evolution in 2D vdW materials. 46–51 There have been several review articles covering the role of geometries, energetics and stabilities of different edges of 2D nuclei and also on the role of different growth parameters ( e.g.…”
Section: Driving Forces For the On-substrate Nucleation And Growth Of...mentioning
confidence: 99%
“…H-BN is generally prepared on the catalytically active metal materials (such as Cu, Ni, Co, Pt, etc. ), and the research on the interface interaction with the substrate has been widely explored 5 , 6 . For example, Lin’s team demonstrated that the weak interaction between hexagonal boron nitride nanosheets (h-BNNSs) and Cu (111) substrates allows the transfer of electrons from h-BN/Cu (111) to adsorbed oxygen molecules, leading to its activation 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of dimensionality can result in notable deviations in the material's properties from their bulk counterparts, often exhibiting unique or unexpected characteristics. For example, two-dimensional (2D) graphene exhibits exceptional electrical and thermal conductivity as well as extraordinary mechanical strength, doped 2D h -BN demonstrates unusual optical and magnetic behaviors, and 2D metal dichalcogenides show auspicious tunable band gap energies and catalytic edge effects. Piezoelectricity is another interesting and significant trait of 2D materials because it enables the transfer of energy between electrical and mechanical forms.…”
Section: Introductionmentioning
confidence: 99%